Sistem Pendeteksi Kebocoran Gas LPG berbasis Internet of Things - Jasmawati, Jasmawati; Wahyuddin, Wahyuddin; Andrian, Andrian (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2024)
The background of this research is the frequent occurrence of LPG gas leaks where when it occurs, no one is at home so that no one can close or disconnect the gas line. This can trigger a fire or the gas will run out wasted. Based on this background, the purpose of this research is to design a gas leak prevention system that can be connected to a smartphone. By using experimental research, namely system design and manufacturing of tools as research media, the authors created an internet-based LPG gas leak detection system of things. The data was obtained by means of library research, namely collecting references from various sources related to the research being carried out, and measuring the output on the device made of several components, namely MQ2 to detect gas ppm, load cell to read gas weight, buzzer to notify gas leaks, and servo motor to remove the gas regulator as well as the interconnection in the application (regulator safety). The parameters used for analysis are the ppm value for detecting gas leaks, the weight of gas cylinders, notifications and monitoring of gas leaks in applications. The results showed that from the data from the black box test results obtained which showed the performance of the tool was working properly, and on testing each component it also showed that it had worked according to its function, and testing on applications could bring up gas leak notifications as well as monitoring ppm and gas weight . Based on the overall system testing, it can be concluded that the tool made, namely the internet of things based LPG gas leak detection system, is running well.